2016
DOI: 10.1016/j.ijimpeng.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Energy absorption in lattice structures in dynamics: Experiments

Abstract: Article available under the terms of the CC-BY-NC-ND licence (https://creativecommons.org/licenses/by-nc-nd/4.0/) eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 238 publications
(94 citation statements)
references
References 19 publications
3
89
0
2
Order By: Relevance
“…Specifically, the forces at the frontface of the HC1 and LC1 specimen is higher than the forces in the back-face, which is an indication of localized deformation. The progressive damage behavior in lattices has been previously observed in other studies [9,5] which are also associated with imbalance of forces in the lattice. Figure 9(a, b) show the results of FE simulations of the HC1 specimen under dynamic load where the coefficient of friction between the specimen and the top and bottom plates are assumed to be (i) equal and (ii) different, respectively.…”
Section: Finite Element Analysissupporting
confidence: 71%
See 1 more Smart Citation
“…Specifically, the forces at the frontface of the HC1 and LC1 specimen is higher than the forces in the back-face, which is an indication of localized deformation. The progressive damage behavior in lattices has been previously observed in other studies [9,5] which are also associated with imbalance of forces in the lattice. Figure 9(a, b) show the results of FE simulations of the HC1 specimen under dynamic load where the coefficient of friction between the specimen and the top and bottom plates are assumed to be (i) equal and (ii) different, respectively.…”
Section: Finite Element Analysissupporting
confidence: 71%
“…They concluded that the elastic properties of periodic lattice structures can be predicted accurately by the Bloch wave theory. Ozdemir et al [9] studied energy absorption of lattice structures under quasi-static and dynamic loading. Cubic, diamond, and reentrant cube additively manufactured lattice structures were tested under quasistatic and dynamic loads and it was observed that lattice structures are able to spread impact loading in time and to reduce the peak impact stress.…”
Section: Introductionmentioning
confidence: 99%
“…The method has been used for the production of Ti lattices of various designs including those based on unit cells with structures of diamond [79] , cubes [79,80] and more complex cubic-based designs [79] as well as rhombic dodecahedron [81] .…”
Section: Metal Injection Moulding With Space Holder (Mim-sh)mentioning
confidence: 99%
“…Random structured sponges have been tested, showing that plastic collapse happened at all strain rates, but with a higher fraction of cracking at high speeds, and that samples showed strain rate sensitivity, which was affected by the density, and thus the foam structure [123,124] experimental studies of high speed impact of Ti lattices (Fig. 15) have shown that there is a protective effect, and emergent rate dependence due to the structure, indicating that design of structures could tailor the response [79] . …”
Section: Impactmentioning
confidence: 99%
“…In general, lattice structures are referred as a cellular solid which can be categorized into stochastic structures (foam) and non-stochastic structures [5]. Lattice structure is also suitable to be used as ultralight structures, conformal cooling, low thermal expansion structures and energy absorber [6][7][8][9] in automotive industry. It is widely used in a biomedical application such as tissue engineering and orthopedic implant [10][11].…”
Section: Introductionmentioning
confidence: 99%